Sense of Smell as the Central Driver of Pavlovian Appetite Behavior in Mammals - Fine, Leon G.; Riera, Celine E. (Frontiers in Physiology, 2019)
The seminal experiments of Ivan Petrovich Pavlov set the stage for an understanding of the physiological concomitants of appetite and feeding behavior. His findings, from careful and creative experimentation, have been uncontested for over a century. One of Pavlov’s most fundamental observations was that activation of salivary, gastric and pancreatic secretions during feeding and sham-feeding, precedes entry of food into the mouth, generating signals to the brain from various sensory pathways. Pavlov referred to this as the “psychic” phase of digestion. However, quite surprisingly, he did not attempt to isolate any single sensory system as the main driver of this phenomenon. Herein we revisit Pavlov’s findings and hypothesize that the evolutionarily-important sense of smell is the pathway most-likely determinant of feeding behavior in mammals. Substantial understandings of olfactory receptors and their neural pathways in the central nervous system have emerged over the past decade. Neurogenic signals, working in concert with hormonal inputs are described, illustrating the ways in which sense of smell determines food-seeking and food-preference. Additionally, we describe how sense of smell affects metabolic pathways relevant to energy metabolism, hunger and satiety as well as a broad range of human behaviors, thereby reinforcing its central biological role in mammals. Intriguing possibilities for future research, based upon this hypothesis, are raised.